Torsional Vibration Analysis of Reciprocating Compressor Trains driven by Induction Motors. Issue 1 (July 2015) - Brunelli, M; Fusi, A; Grasso, F; Pasteur, F; Ussi, A
Abstract: The dynamic study of electric motor driven compressors, for Oil&Gas (O&G) applications, are traditionally performed in two steps separating the mechanical and the electrical systems. The packager conducts a Torsional Vibration Analysis (TVA) modeling the mechanical system with a lumped parameter scheme, without taking into account the electrical part. The electric motor supplier later performs a source current pulsation analysis on the electric motor system, based on the TVA results. The mechanical and the electrical systems are actually linked by the electromagnetic effect. The effect of the motor air-gap on TVA has only recently been taken into account by adding a spring and a damper between motor and ground in the model. This model is more accurate than the traditional one, but is applicable only to the steady-state condition and still fails to consider the reciprocal effects between the two parts of the system. In this paper the torsional natural frequencies calculated using both the traditional and the new model have been compared. Furthermore, simulation of the complete system has been achieved through the use of LMS AMESim, multi-physics, one-dimensional simulation software that simultaneously solves the shafts rotation and electric motor voltage equation. Finally, the transient phenomena that occur during start-up have been studied.